The Influence of Religious Spiritual-Based Learning Approach to Learning Outcomes of Natural Sciences at Madrasah Tsanawiyah Pekanbaru - Murhayati, Sri; Hartono, Hartono; binti Ramly, Siti Nor Fazila; Syarif, Muhammad Ilham (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study was aimed to reveal the contribution of a spiritual-religious-based learning approach to the learning outcomes of Natural Sciences at Madrasah Tsanawiyah Pekanbaru. To achieve this goal, this study used a quantitative-based approach with correlational research methods. The population of this study were 444 students of class VIII from Madrasah Tsanawiyah in Pekanbaru city with a sample of 211 students selected by cluster sampling technique. Data collection was carried out by conducting a questionnaire to measure the variables of a religious spiritual-based learning approach. Hypothesis testing was carried out using inferential statistical tests with simple correlation. Based on the results of data analysis, it can be concluded that the application of a spiritual-religious-based learning approach in science learning at Madrasah Tsanawiyah Pekanbaru can be categorized as good (70.06%) and students' science learning outcomes are also categorized as good (72.02%). The results of the study found that there was a significant positive contribution from the application of a spiritual-religious-based learning approach to the science learning outcomes of Madrasah Tsanawiyah Pekanbaru students, to be precisely the contribution coefficient obtained was 49%, while 51% was caused by other variables.Keywords: learning approach, spiritual religion, learning outcomes